If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 5 = 137 + -6x Reorder the terms: 5 + 5x = 137 + -6x Solving 5 + 5x = 137 + -6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6x' to each side of the equation. 5 + 5x + 6x = 137 + -6x + 6x Combine like terms: 5x + 6x = 11x 5 + 11x = 137 + -6x + 6x Combine like terms: -6x + 6x = 0 5 + 11x = 137 + 0 5 + 11x = 137 Add '-5' to each side of the equation. 5 + -5 + 11x = 137 + -5 Combine like terms: 5 + -5 = 0 0 + 11x = 137 + -5 11x = 137 + -5 Combine like terms: 137 + -5 = 132 11x = 132 Divide each side by '11'. x = 12 Simplifying x = 12
| 6x=121-5x | | 4x=63-5x | | 9(m-3)+3m=7m+43 | | 3.14x^5-6x^4-9=0 | | 12x-2=7x+23 | | 12x-2=7x+32 | | y=40ln(3x+8) | | 12-2u=8u+45 | | 124-3x=24+19 | | x/4+x+5/3=4 | | x-1/2x+x+3/4x=5/8 | | X^3-3x^2-x-3=0 | | 5/x+6=17/x | | x+2y+3z=1 | | 0.2y=3y | | 83-3x=10x+8 | | x=(8n+8n-1)2(4n-4n-1)2 | | 3p^4-8p^2+6=0 | | -5+11=14x-4-13x | | -15-(-31)=x/7 | | -6(t+1)=24 | | 20-14=3(x-2) | | b/7-18=-20 | | x+24+3x=-7-3x-11 | | c/8+3=7 | | 5x^2-10x^2=-7+x | | 42=30-m | | h/3+15=41 | | 4n-3=5n-5 | | -14x-20=12x+90 | | 76=58+9d | | 4(a-2)=16 |